Question and Answers Forum

All Questions      Topic List

Differentiation Questions

Previous in All Question      Next in All Question      

Previous in Differentiation      Next in Differentiation      

Question Number 188033 by Michaelfaraday last updated on 25/Feb/23

from first principle  y=xInx  find (dy/dx)

$${from}\:{first}\:{principle} \\ $$$${y}={xInx}\:\:{find}\:\frac{{dy}}{{dx}} \\ $$

Answered by a.lgnaoui last updated on 25/Feb/23

(dy/dx)=lnx+1=(y/x)+1  (y/x)=(dy/dx)−1⇒  (dy/dx)−(y/x)−1=0(equation dif)

$$\frac{{dy}}{{dx}}={lnx}+\mathrm{1}=\frac{{y}}{{x}}+\mathrm{1} \\ $$$$\frac{{y}}{{x}}=\frac{{dy}}{{dx}}−\mathrm{1}\Rightarrow \\ $$$$\frac{{dy}}{{dx}}−\frac{{y}}{{x}}−\mathrm{1}=\mathrm{0}\left({equation}\:{dif}\right) \\ $$$$ \\ $$

Commented by Spillover last updated on 25/Feb/23

from the first priciple  f^′ (x)=lim_(h→0) ((f(x+h)−f(x))/h)

$${from}\:{the}\:{first}\:{priciple} \\ $$$${f}^{'} \left({x}\right)=\underset{{h}\rightarrow\mathrm{0}} {\mathrm{lim}}\frac{{f}\left({x}+{h}\right)−{f}\left({x}\right)}{{h}} \\ $$

Answered by Mr_X last updated on 25/Feb/23

Solution ⇒  y=xln(x)  ⇒ y+Δy=(x+Δx)[ln(x+Δx)]  ⇒ Δy=(x+Δx)[ln(x+Δx)]−xln(x)  ⇒ Δy=(x+Δx){ln[(x)(1+((Δx)/x))]}−xln(x)  ⇒ Δy=(x+Δx)[ln(x)+ln(1+((Δx)/x))]−xln(x)  ⇒ Δy=xln(x)+Δxln(x)+xln(1+((Δx)/x))+Δxln(1+((Δx)/x))−xln(x)  ⇒ ((Δy)/(Δx))=ln(x)+(x/(Δx))ln(1+((Δx)/x))+ln(1+((Δx)/x))  ⇒ ((Δy)/(Δx))=ln(x)+ln[(1+((Δx)/x))]^(x/(Δx)) +ln(1+((Δx)/x))  ⇒ lim_(Δx→0) ((Δy)/(Δx))=ln(x)+lim_(Δx→0) ln[(1+((Δx)/x))]^(x/(Δx)) +lim_(Δx→0) ln(1+((Δx)/x))  ⇒ (dy/dx)=ln(x)+ln[lim_(Δx→0) (1+((Δx)/x))]^(x/(Δx)) +lim_(Δx→0) ln(1+((Δx)/x))  ⇒ (dy/dx)=ln(x)+ln(e)+ln(1)  ⇒ (dy/dx)=ln(x)+1+0  or  ⇒ (dy/dx)=ln(x)+1

$${Solution}\:\Rightarrow \\ $$$${y}={xln}\left({x}\right) \\ $$$$\Rightarrow\:{y}+\Delta{y}=\left({x}+\Delta{x}\right)\left[{ln}\left({x}+\Delta{x}\right)\right] \\ $$$$\Rightarrow\:\Delta{y}=\left({x}+\Delta{x}\right)\left[{ln}\left({x}+\Delta{x}\right)\right]−{xln}\left({x}\right) \\ $$$$\Rightarrow\:\Delta{y}=\left({x}+\Delta{x}\right)\left\{{ln}\left[\left({x}\right)\left(\mathrm{1}+\frac{\Delta{x}}{{x}}\right)\right]\right\}−{xln}\left({x}\right) \\ $$$$\Rightarrow\:\Delta{y}=\left({x}+\Delta{x}\right)\left[{ln}\left({x}\right)+{ln}\left(\mathrm{1}+\frac{\Delta{x}}{{x}}\right)\right]−{xln}\left({x}\right) \\ $$$$\Rightarrow\:\Delta{y}={xln}\left({x}\right)+\Delta{xln}\left({x}\right)+{xln}\left(\mathrm{1}+\frac{\Delta{x}}{{x}}\right)+\Delta{xln}\left(\mathrm{1}+\frac{\Delta{x}}{{x}}\right)−{xln}\left({x}\right) \\ $$$$\Rightarrow\:\frac{\Delta{y}}{\Delta{x}}={ln}\left({x}\right)+\frac{{x}}{\Delta{x}}{ln}\left(\mathrm{1}+\frac{\Delta{x}}{{x}}\right)+{ln}\left(\mathrm{1}+\frac{\Delta{x}}{{x}}\right) \\ $$$$\Rightarrow\:\frac{\Delta{y}}{\Delta{x}}={ln}\left({x}\right)+{ln}\left[\left(\mathrm{1}+\frac{\Delta{x}}{{x}}\right)\right]^{\frac{{x}}{\Delta{x}}} +{ln}\left(\mathrm{1}+\frac{\Delta{x}}{{x}}\right) \\ $$$$\Rightarrow\:\underset{\Delta{x}\rightarrow\mathrm{0}} {{lim}}\frac{\Delta{y}}{\Delta{x}}={ln}\left({x}\right)+\underset{\Delta{x}\rightarrow\mathrm{0}} {{lim}ln}\left[\left(\mathrm{1}+\frac{\Delta{x}}{{x}}\right)\right]^{\frac{{x}}{\Delta{x}}} +\underset{\Delta{x}\rightarrow\mathrm{0}} {{lim}ln}\left(\mathrm{1}+\frac{\Delta{x}}{{x}}\right) \\ $$$$\Rightarrow\:\frac{{dy}}{{dx}}={ln}\left({x}\right)+{ln}\left[\underset{\Delta{x}\rightarrow\mathrm{0}} {{lim}}\left(\mathrm{1}+\frac{\Delta{x}}{{x}}\right)\right]^{\frac{{x}}{\Delta{x}}} +\underset{\Delta{x}\rightarrow\mathrm{0}} {{lim}ln}\left(\mathrm{1}+\frac{\Delta{x}}{{x}}\right) \\ $$$$\Rightarrow\:\frac{{dy}}{{dx}}={ln}\left({x}\right)+{ln}\left({e}\right)+{ln}\left(\mathrm{1}\right) \\ $$$$\Rightarrow\:\frac{{dy}}{{dx}}={ln}\left({x}\right)+\mathrm{1}+\mathrm{0} \\ $$$${or} \\ $$$$\Rightarrow\:\frac{{dy}}{{dx}}={ln}\left({x}\right)+\mathrm{1} \\ $$

Commented by Michaelfaraday last updated on 01/Mar/23

thanks sir

$${thanks}\:{sir} \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com